Development and characterization of fiber-reinforced biopolymer composites from rice husk waste with Rhizopus oligosporus as a bio-binder - Mohammad Aliff Shakir; Mardiana Idayu Ahmad; Azniwati Abd Aziz; Abdul Khalil H.P.S. (eXPRESS Polymer Letters, 2025)
The growing demand for eco-friendly alternatives to synthetic polymers has accelerated interest in fibrous, cellulose-rich waste as a foundation for sustainable composite materials. Agricultural waste like rice husk offers abundant, renewable sources of natural polymers suitable for advanced biocomposite development. However, the integration of such materials often requires innovative bonding approaches, particularly those that are biodegradable and derived from renewable sources. This study explores the use of rice husk fibers with Rhizopus oligosporus mycelium as a bio-binder by examining how varying inoculation durations (0, 2, 4, and 6 days) affect the mechanical and physical characteristics of the composite. The prepared samples underwent hot pressing at 130°C and 5 MPa for 30 min. Visual and morphological analyses confirmed that longer inoculation periods promoted denser and more uniform mycelial growth, improving adhesion within the composite matrix. Results revealed that the composite with 4 days of inoculation exhibited the best overall physical and mechanical properties with flexural strength (5.79 MPa), tensile strength (2.59 MPa), water absorption (112.1%), contact angle (39.99°) and thickness swelling (126.33%). These findings demonstrate the feasibility of repurposing cellulose-rich agricultural waste into functional fibrous polymer composites, supporting sustainable material development and contributing to polymer recycling efforts.